Hypoxia signaling pathway: A central mediator in endocrine tumors - Watts, Deepika; Jaykar, Mangesh T.; Bechmann, Nicole; Wielockx, Ben (Frontiers in Endocrinology, 2023)
Adequate oxygen levels are essential for the functioning and maintenance of biological processes in virtually every cell, albeit based on specific need. Thus, any change in oxygen pressure leads to modulated activation of the hypoxia pathway, which affects numerous physiological and pathological processes, including hematopoiesis, inflammation, and tumor development. The Hypoxia Inducible Factors (HIFs) are essential transcription factors and the driving force of the hypoxia pathway; whereas, their inhibitors, HIF prolyl hydroxylase domain (PHDs) proteins are the true oxygen sensors that critically regulate this response. Recently, we and others have described the central role of the PHD/HIF axis in various compartments of the adrenal gland and its potential influence in associated tumors, including pheochromocytomas and paragangliomas. Here, we provide an overview of the most recent findings on the hypoxia signaling pathway in vivo, including its role in the endocrine system, especially in adrenal tumors.